Who Controls Women's Pilgrimage? Gender Equity and the Administrative Dynamics of Hajj in Turkey - Zahriani Anugerah Arman (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2026)
This paper analyses the governance of women's access to Hajj in Turkey, emphasising the interplay of gender, authority, and administrative regulation. Traditional discussions have focused on doctrinal matters like the necessity of a male guardian, but modern governance structures have transitioned authority to bureaucratic processes. This research employs a qualitative socio-legal methodology, utilising policy analysis, institutional data, and interviews with female pilgrims to investigate the structuring and experience of access. The results indicate that despite the elimination of overt gender-based limitations, participation is influenced by administrative mechanisms including registration procedures, quota distribution, and waiting periods. This transformation signifies a shift of authority from religious interpretation to state control, especially via institutions like the Diyanet. The research indicates that women's agency is not entirely autonomous but rather negotiated within institutional restrictions. This research elucidates the functioning of control inside administrative systems, thus advancing the notion of gender justice from mere legal equality to structural access. It enhances socio-legal and gender studies by providing a sophisticated comprehension of the politics of Islamic administration in modern Muslim cultures.